SAY NO TO INFLATION TARGETING: A CALL FOR THE ADAPTATION OF A ZERO-INTEREST REGIME - Rehman, Atiq ur (Bank Indonesia, 2021)
In its early history, monetary policy focused on numerous objectives, including stable growth, full employment, stable exchange rates and price stability. In the 1990s, many countries shifted their monetary policy framework from monetary aggregate/interest rate targeting to inflation targeting, in which inflation was regarded as the primary target of monetary policy, and interest rates the primary tool for achieving target inflation. Inflation targeting has diverted the focus of central banks from growth and employment to price stability. Unfortunately, there is considerable evidence which shows that inflation targeting frameworks are unable to control inflation in the way central banks want, and in fact lead to a greater departure from optimal growth and employment, the two key targets of sustainable development goals (SDGs). There is also evidence suggesting a strong association between inflation targeting and the move away from several other SDGs. Employing a systematic review of the related literature and Granger causality tests applied to data from various countries, this paper shows that inflation targeting fails to control inflation and has several undesirable impacts on a wide range of socioeconomic indicators. It is argued that the zero-interest regime is the optimal regime with respect to the impact on socioeconomic indicators, and also supports the interest free economy advocated by Islam.